Music Therapy and Culture: An Essential Relationship? - Daisy Morris (Approaches: Music Therapy & Special Music Education, 2010)
Whilst being interviewed by Brynjulf Stige for the Nordic Journal of Music Therapy (volume 10, issue 1), Kenneth Aigen said “I do not think it is reasonable to think that we could automatically work with someone from a very different culture” (Aigen 2001: 90). Standing alone, this passage spoken by Aigen may give a negative impression. This paper will aim to put the above statement in context and think carefully about what Aigen might be suggesting. Through an honest and open exploration of the questions the statement raises, a realistic and more optimistic dialogue which was hidden beneath the words is unearthed. Through the deconstruction of Aigen’s statement this paper investigates our attitudes as music therapists towards culture and music and the preconceptions and assumptions which may arise. This paper will stress how a willingness to explore and broaden not only our attitudes towards culture, but also the confines of our musical ability, can result in an expansion of our knowledge, awareness and receptiveness. This, in turn, could lead to a practice of music therapy which is more fruitful and successful, one in which we are clinically open and prepared for whatever our clients might bring to or need from their sessions.